Kepuasan Pengguna Aplikasi Pembayaran online ditinjau dari Kemudahan Penggunaan dan Pengalaman Berbelanja - Nuryani; Arjuna Wiwaha; Wenny Chandra Mandagie (STIE-JIC, 2022)
The Indonesian demand for online payment services keeps rising steadily. Consequently, various new applications have sprung up, including Sepulsa and OVO. However, the success of companies providing these services largely depends on the user satisfaction factor along with ease of use to determine their shopping experience. This research aimed to determine the effect of ease of use and shopping experience on user satisfaction derived from Sepulsa and OVO online payment applications. The data from a sample size of 105 respondents drawn from Jakarta was collected using questionnaires distributed through Google Form. The data collected was then processed using regression and correlation methods with the help of SPSS 25 software. The results concluded that user satisfaction on Sepulsa and OVO applications was 72.8% jointly shared by the ease of use and shopping experience, while 27.2% is represented by factors/variables, which were not covered in this research. This calls for online payment application companies to improve their services.